Selection of eco-friendly materials for grocery store packaging - Chebotarova, I.; Striliana, К.; Vovk, O.; Dovgal, А.; Chebotarоva, М. (ТОВ «Друкарня Мадрид», 2024)
As the volume of production of various products increases, more packaging is needed. This trend is one of the most important causes of environmental damage. Attractive, resistant and informative packaging is not only used to protect products, but is also an essential attribute of marketing promotion. Almost all products on store shelves are wrapped in many layers of paper, film, and plastic, which are thrown away by consumers immediately after use.
Keywords: materials; packaging